Evaluasi Kinerja Karyawan Berbasis Digital Sebagai Fondasi Pengembangan SDM Pada Era Society 5.0 - Triliani Krismidasi; Zakky Zamrudi; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The development of Society 5.0 requires organizations to integrate digital technologies into their performance evaluation systems as part of human resource development strategies. This study aims to examine the role of digital-based performance evaluation in supporting HR development in the era of Society 5.0 through a Systematic Literature Review (SLR) approach. Data were obtained from various international and national publications published between 2020 and 2025. The findings show that the implementation of digital performance evaluation enhances assessment objectivity, accelerates decision-making, and strengthens human resource competency development planning. However, its implementation still faces challenges, including data integration, digital literacy, and ethical considerations. These findings emphasize that digital evaluation systems can serve as a strategic foundation for adaptive and sustainable HR development in the Society 5.0 era.